Effects of pedagogical gestures on learning abstract grammatical concepts in young adults - Lopez-Ozieblo, Renia (Frontiers in Communication, 2024)
This study evaluates the benefits of gesture-enriched grammatical explanations to native speakers following an embodied cognitive approach. Spanish mother tongue speakers were taught the functions of a complex Spanish linguistic unit, 'se'. For half the participants the explanations were enhanced with gestures and the other half received the same explanations without gestures. Their knowledge of the functions was tested before the treatment and then immediately after and a month after the treatment. Our results indicate that both groups benefitted from the explanations equally.However, in the long-term participants in the gestures group consolidated their knowledge while those in the non-gestures group showed a steeper learning decay that those in the gestures group. This suggests that gestures might have a positive effect in learning which is only observable in the long-term after the knowledge has been consolidated.